Marketing strategies of multinational enterprises and their adaption to culturally distant host countries - Mdladla, Ntandokayise (Graduate School of Business (GSB), 2024)
This research study explored how multinational enterprises (MNEs) adapt their marketing strategies to the level of cultural distance in their host countries. The research topic is relevant today as companies continue to expand their reach and enter countries which may have a high level of cultural distance compared to the home country. The research explored the marketing strategies of MNEs, for instance how different organisational communication structures such as a centralised and decentralised approach can impact the marketing communications of a company and their adaptation to different levels of cultural distance in host countries. To gain a more in-depth understanding, a qualitative and exploratory research was undertaken, and the case study approach was selected in analysing an advertising campaign in West Africa. Semi-structured interviews were conducted with experts within the marketing industry and employees within an MNE. The findings showed certain themes that came up in relation to the topic as found through the interviews. These included the generational difference in views on culturally or racially insensitive advertisements, how social media has possibly fuelled sensitivity to such advertisements, how the composition of the team could impact a company's ability to adapt to countries with a high level of cultural distance, and how the organisational structure of a company can impact the marketing communications of the company. It was found that a company's ability to adapt their marketing strategies to countries with a high level of cultural distance is also dependent on many factors, as identified in the themes previously listed, and to look at just the cultural distance in the Hofstede's model in isolation may prove more as a way an MNE may start to understand the impact of cultural distance and not an overall way in which to understand its impact on the marketing strategies. Culture distance is a topic that shall remain relevant to businesses that continue to expand their operations into different countries of the world. Therefore, this research explored how MNEs can adapt to the level of cultural distance and its role in their marketing strategies